Endothelial leukocyte adhesion molecule-1 mediates antigen-induced acute airway inflammation and late-phase airway obstruction in monkeys. - Gundel, R H; Wegner, C D; Torcellini, C A; Clarke, C C; Haynes, N; Rothlein, R; Smith, C W; Letts, L G (The Journal of Clinical Investigation, 1991)
This study examines the role of endothelial leukocyte adhesion molecule-1 (ELAM-1) in the development of the acute airway inflammation (cell influx) and late-phase airway obstruction in a primate model of extrinsic asthma. In animals sensitive to antigen, a single inhalation exposure induced the rapid expression of ELAM-1 (6 h) exclusively on vascular endothelium that correlated with the influx of neutrophils into the lungs and the onset of late-phase airway obstruction. In contrast, basal levels of ICAM-1 was constitutively expressed on vascular endothelium and airway epithelium before antigen challenge. After the single antigen exposure, changes in ICAM-1 expression did not correlate with neutrophil influx or the change in airway caliber. This was confirmed by showing that pretreatment with a monoclonal antibody to ICAM-1 did not inhibit the acute influx of neutrophils associated with late-phase airway obstruction, whereas a monoclonal antibody to ELAM-1 blocked both the influx of neutrophils and the late-phase airway obstruction. This study demonstrates a functional role for ELAM-1 in the development of acute airway inflammation in vivo. We conclude that, in primates, the late-phase response is the result of an ELAM-1 dependent influx of neutrophils. Therefore, the regulation of ELAM-1 expression may provide a novel approach to controlling the acute inflammatory response, and thereby, affecting airway function associated with inflammatory disorders, including asthma. Images